Lespedeza bicolor Extract Ameliorated Renal Inflammation by Regulation of NLRP3 Inflammasome-Associated Hyperinflammation in Type 2 Diabetic Mice - Ji Eun Park; Heaji Lee; Sun Yeou Kim; Yunsook Lim (MDPI AG, 2020)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder characterized by hyperglycemia. The chronic hyperglycemic condition causes hyperinflammation via activation of nucleotide-binding oligomerization domain-like pyrin domain containing receptor 3 (NLRP3) inflammasome and abnormally leads to morphological and functional changes in kidney. A previous study showed a protective effect of Lespedeza bicolor extract (LBE) on endothelial dysfunction induced by methylglyoxal glucotoxicity. We aimed to investigate whether LBE ameliorated renal damage through regulation of NLRP3 inflammasome-dependent hyper-inflammation in T2DM mice. After T2DM induction by a high fat diet and low dose of streptozotocin (30 mg/kg), the mice were administered with different dosages of LBE (100 or 250 mg/kg/day) by gavage for 12 weeks. LBE supplementation ameliorated kidney dysfunction demonstrated by urine albumin-creatinine at a low dose and plasma creatinine, blood urea nitrogen (BUN), and glomerular hypertrophy at a high dose. Furthermore, a high dose of LBE supplementation significantly attenuated renal hyper-inflammation associated with NLRP3 inflammasome and oxidative stress related to nuclear factor erythroid 2-related factor 2 (Nrf-2) in T2DM mice. Meanwhile, a low dose of LBE supplementation up-regulated energy metabolism demonstrated by phosphorylation of adenosine monophosphate kinase (AMPK) and Sirtuin (SIRT)-1 in T2DM mice. In conclusion, the current study suggested that LBE, in particular, at a high dose could be used as a beneficial therapeutic for hyperglycemia-induced renal damage in T2DM.